The conception of the character in A. Miller’s The Last Yankee (Eurasian Journal of Philology Science and Education, 2016)
The article is devoted to the little known in Kazakhstan A. Miller’s play The Last Yankee which has not been translated into Russian yet. In the article the author attempts to analyze the play’s conception of the character, the main problem of the play and the role of the heroes in the development of the author’s conception. The main problem of the play, according to Miller’s own words is the problem of «what would once have been called a sickness of the soul», and this problem develops through the play with the help of Miller’s heroes. The play is written in the realistic manner. The main artistic achievement in the play is its deep psycologism.
Keywords: drama; psychoanalysis; human phenomenon; the problem; the intellectual theater; the idea of creative evolution; genre; composition; subject.